Anolis marsupialis Taylor 1956, a valid species from southern Pacific Costa Rica (Reptilia, Squamata, Dactyloidae) - Köhler, Johannes J.; Poe, Steven; Ryan, Mason J.; Köhler, Gunther (Zootaxa, 2015)
The examination of the holotype of Anolis marsupialis Taylor 1956 along with recently collected specimens reveals that A. marsupialis is a valid species. It differs from its closest congeners A. humilis Peters 1863 and A. quaggulus Cope 1885, in male dewlap coloration, scalation, body size, and hemipenial morphology. These findings are supported by preliminary molecular genetic analysis.